Reinforcing the generic status of Discina: Morphological and phylogenetic evidence with new records from Türkiye - Gungor, Mihrican Yaratanakul; Gongor, Halil; Turkekul, Ibrahim (Phytotaxa, 2025)
Recent molecular studies have significantly reshaped the taxonomy of the family Discinaceae (Pezizales, Ascomycota), leading to the redefinition of several genera, including Discina and the recently described Maublancomyces. Despite these advances, regional records and phylogenetic placements of many taxa remain poorly documented. In this study, we report two new national records from Türkiye: Discina macrospora and Maublancomyces apiculatulus. We combined detailed morphological descriptions with ITS-based phylogenetic analyses to confirm their identity and clarify their systematic positions within Discinaceae. Our results strongly support the distinct generic status of Discina and Maublancomyces, in agreement with recent phylogenetic studies. Phylogenetic trees constructed via maximum likelihood methods revealed high bootstrap support for the monophyly of all major genera within the family, including Discina, Maublancomyces, and Paradiscina, the latter of which we propose should remain within Discinaceae. This study contributes to the mycobiota of Türkiye and provides new molecular data to GenBank, reinforcing the taxonomy of Discina and Maublancomyces.